2019
DOI: 10.3928/19382359-20191018-01
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Malnutrition in Children

Abstract: Exocrine pancreatic insufficiency in children can lead to lifelong complications related to malnutrition and poor growth. The clinical presentation can be subtle in the early stages of insufficiency as the large functional capacity of the pancreas is gradually lost. The pediatrician plays a crucial role in the early identification of these children to ensure a timely referral so that a diagnosis can be made and therapy initiated. Early nutritional therapy allows for prevention and correction of deficiencies, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
0
2
Order By: Relevance
“…The total average content is higher than published research because previous studies identified fewer phospholipid molecular species . The steady content of total phospholipids at various phases (colostrum, transitional milk, and mature milk) of lactation was important to provide normal fat digestion and absorption for the neonates, whose secretion of the pancreas might be defective . However, the studies of Ma et al and Zhao et al revealed that the content of total phospholipids from colostrum to mature milk declined, which was not steady like this research.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…The total average content is higher than published research because previous studies identified fewer phospholipid molecular species . The steady content of total phospholipids at various phases (colostrum, transitional milk, and mature milk) of lactation was important to provide normal fat digestion and absorption for the neonates, whose secretion of the pancreas might be defective . However, the studies of Ma et al and Zhao et al revealed that the content of total phospholipids from colostrum to mature milk declined, which was not steady like this research.…”
Section: Resultscontrasting
confidence: 56%
“…19 The steady content of total phospholipids at various phases (colostrum, transitional milk, and mature milk) of lactation was important to provide normal fat digestion and absorption for the neonates, whose secretion of the pancreas might be defective. 28 However, the studies of Ma et al 29 and Zhao et al 20 revealed that the content of total phospholipids from colostrum to mature milk declined, which was not steady like this research. Zhao et al 20 used the reverse-phase liquid chromatography (RPLC) approach to analyze SM, and the content of SM in colostrum was 11.56−153.92 mg/L.…”
Section: Evaluation Of the Total Content Of Human Milk Phospholipidscontrasting
confidence: 43%